Effects of Active Filler Selection on Foamed Bitumen Mixture in Western Australia - Huan, Yue; Jitsangiam, Peerapong; Nikraz, Hamid (Trans Tech Publications, 2011)
This study investigated the effects of different active filler types and contents on the mechanical properties of foamed bitumen treated materials under laboratory conditions. Four different active fillers were tested namely Portland cement, hydrated lime, quicklime and fly ash, at varying concentration of 0%, 1%, 3% and 5%. To evaluate the effects of the additional active fillers, samples were prepared under laboratory conditions and tested using indirect tensile strength, indirect tensile resilient modulus and unconfined compressive strength tests. Based upon our findings, all active filler types except fly ash contributed in improving the strength of foamed bitumen mixtures at different levels. Cement, regardless of adding contents, always provided the highest mechanical performance compared with the other two counterparts: hydrated lime and quicklime. Fly ash was deliberated to be precluded because fly ash on its own did not affect any mechanical strength of foamed bitumen mixesinsteadit acted as a mineral filler to modify aggregate gradation. The addition of active filler content should be limited within 3% in terms of strength gain and potential cracking prevent when mixing with 4% foamed bitumen content and locally sourced raw materials for base course.